2006
DOI: 10.1080/10915810500488379
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Glulisine—A Comprehensive Preclinical Evaluation

Abstract: Receptor binding and signaling and the mitogenic potential of insulin glulisine (glulisine), regular human insulin (RHI), and Asp(B10) were compared in vivo and in vitro. Insulin and insulin-like growth factor 1 (IGF-1) receptor binding was studied with human insulin receptors (293HEK cells) and the human osteosarcoma-derived cell line B10. Insulin receptor-mediated signaling was assessed in rat-1 fibroblasts overexpressing insulin receptors. Activation of insulin receptor substrates 1 and 2 (IRS-1/ IRS-2) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…The relevance of hybrid receptors remains to be investigated (Frasca et al, 2008), and IR affinity may remain low in the presence of enhanced IFG-I-R affinity (Slaaby et al, 2006) The guideline (EMEA 2001) recommends reference compounds which were already included in many investigations (Baehr et al, 1997;Berti et al, 1998;Hennige et al, 1999;Kellerer & Haering, 2001, Ciaraldi et al, 2001. In the non-clinical evaluation of insulin glargine and glulisine, human insulin, [B10-Asp] and IGF-I were included when investigating the insulin receptor association and dissociation kinetics, and binding affinities for the IR and IGF-I-R (Stammberger et al, 2006). A note of caution concerns the interpretation of mitogenic potential (carcinogenicity).…”
Section: Clinically Used Insulinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of hybrid receptors remains to be investigated (Frasca et al, 2008), and IR affinity may remain low in the presence of enhanced IFG-I-R affinity (Slaaby et al, 2006) The guideline (EMEA 2001) recommends reference compounds which were already included in many investigations (Baehr et al, 1997;Berti et al, 1998;Hennige et al, 1999;Kellerer & Haering, 2001, Ciaraldi et al, 2001. In the non-clinical evaluation of insulin glargine and glulisine, human insulin, [B10-Asp] and IGF-I were included when investigating the insulin receptor association and dissociation kinetics, and binding affinities for the IR and IGF-I-R (Stammberger et al, 2006). A note of caution concerns the interpretation of mitogenic potential (carcinogenicity).…”
Section: Clinically Used Insulinsmentioning
confidence: 99%
“…In the case of the [B10-Asp] insulin, results became available when phase-2 studies were already well under way. It is now recommended to use a 6-12 months treatment protocol including proliferation markers in the tissues investigated (Stammberger et al, 2006), preferentially mammary gland tissue based on the experience with [B10-Asp] insulin. Several studies have shown an increase of benign and malignant mammary tumours at supra-physiological doses: [B10-Asp] insulin in Sprague-Dawley rats increased the number of mammary tumours in females (not in males), high dose treatment with human insulin and the fast acting (B29-Asp) insulin increased the number of benign and malignant mammary tumours in studies with 100-fold physiological concentration for 12 months (EMEA, 2004a, b).…”
Section: Mammary Tumours In Rodentmentioning
confidence: 99%
“…The insulin lispro shows an increased affinity for IGF1R and a reduced affinity for IR-A compared with native insulin, but its mitogenic response is similar to that of insulin. The analog aspart is more potent than native insulin in inducing proliferative effects in vitro, whereas the insulin glulisine does not promote any growth advantage to non-malignant mammary cells comparing to the native insulin (Stammberger et al 2006). Clinical studies on cancer risk in diabetic patients have not focused on the use of these analogs.…”
Section: Therapeutical Implications Of Ir Involvement In Cancer Diabementioning
confidence: 99%
“…Insulin glulisine has similar or slightly less binding affinity for the IR than human insulin. In addition, it has been suggested that IGF1R binding affinity is significantly lower than that of human insulin (Stammberger et al 2006). …”
Section: Rapid-acting Insulin Analoguesmentioning
confidence: 99%